Lectotypification of ninie binomials proposed for Sorocea (Moraceae) - Mattos, Leticia De; Gaglioti, André Luiz; Zamengo, Henrique Borges; Pederneiras, Leandro Cardoso; Silva, Paulo Roberto Da; Romaniuc-Neto, Sergio (Phytotaxa, 2026)
N/A